Local delivery of doxorubicin through supramolecular peptide amphiphile nanofiber gels. (7th November 2016) - Cinar, Goksu; Ozdemir, Ayse; Hamsici, Seren; Gunay, Gokhan; Dana, Aykutlu; Tekinay, Ayse B.; Guler, Mustafa O.
Abstract : The local in vivo injection of a Dox encapsulated PA gel to the tumor site demonstrated the lowest tumor growth rate. Abstract : Peptide amphiphiles (PAs) self-assemble into supramolecular nanofiber gels that provide a suitable environment for encapsulation of both hydrophobic and hydrophilic molecules. The PA gels have significant advantages for controlled delivery applications due to their high capacity to retain water, biocompatibility, and biodegradability. In this study, we demonstrate injectable supramolecular PA nanofiber gels for drug delivery applications. Doxorubicin (Dox), as a widely used chemotherapeutic drug for breast cancer treatment, was encapsulated within the PA gels prepared at different concentrations. Physical and chemical properties of the gels were characterized, and slow release of the Dox molecules through the supramolecular PA nanofiber gels was studied. In addition, the diffusion constants of the drug molecules within the PA nanofiber gels were estimated using fluorescence recovery after the photobleaching (FRAP) method. The PA nanofiber gels did not show any cytotoxicity and the encapsulation strategy enhanced the activity of drug molecules on cellular viability through prolonged release compared to direct administration under in vitro conditions. Moreover, the local in vivo injection of the Dox encapsulated PA nanofiber gels (Dox/PA) to the tumor site demonstrated the lowest tumor growth rate compared to the direct Dox injection and increased the apoptotic cells within the tumor tissue for local drug release through the PA nanofiber gels under in vivo conditions.